The revival of Nawruz in Kurdistan-Iraq and the stance of Iraqi regimes from 1921 till 1970 against it. - Mohammed, Sherzad Zakaria; Yousif, Khalat M (Humanities Journal of University of Zakho, 2018)
Nawruz is an ancient festival celebrated mostly by nations who share Aryan race roots including the Kurds. This festival is considered part of their culture, and heritage. It has been revived for hundreds of years due to its importance in terms cultural, historical, ethnical, religious, and geographical dimensions. Festival’s celebration has faced many obstacles throughout the history. The enemies of the Kurds has exerted tremendous efforts for the sake of distancing the Kurds from Nawruz using many false political, ethnical, and religious pretensions. This Festival is extremely significant for the Kurds as it marks the beginning of Kurdish New Year, the start of a new season, and fighting for freedom against oppression and tyranny. Despite all the constraints which were put by subsequent Iraqi regimes to prevent the revival of Nawruz, especially in the 1930s and later in the 20thcentury, nevertheless the Kurds in northern Iraq have shown great resilient spirits and celebrated it in secret and public. For this, they have endured lots pain and sacrifices.